Idiopathic Raynaud’s Phenomenon and Vitamin D Deficiency in Children and Adolescents: An Exploratory Single-Center Retrospective Observational Study Throughout the Period 2010–2025 - Donato Rigante; Michele Fastiggi; Cristina Guerriero; Marcello Candelli (Journal of Clinical Medicine, 2026)
Background: Raynaud’s phenomenon (RP) may occur in the pediatric age span, sometimes representing the forerunner of devious underlying conditions. Objective: To investigate the prevalence of vitamin D deficiency in a single-center cohort of children and adolescents with idiopathic RP and evaluate changes in RP severity following cholecalciferol supplementation. Patients and Methods: Sixty-one children and adolescents with RP regularly followed at the pediatric rheumatology unit of our University between 2010 and 2025 were retrospectively evaluated. Clinical, laboratory, and nailfold videocapillaroscopy (NVC) findings were collected at baseline; patients were periodically examined for a mean investigation period of 3 ± 1.6 years. RP severity was assessed using the 2-week Raynaud’s Condition Score (RCS). Patients found to have serum 25-hydroxyvitamin D levels < 20 ng/mL received cholecalciferol supplementation for at least 12 weeks. Results: Nineteen out of 61 patients with RP (31.1% of the cohort) had vitamin D deficiency, while other laboratory parameters including inflammatory markers, complement fractions, liver and renal function tests, lipid profile, and autoimmune panel were non-informative. Univariate analysis demonstrated significant differences between vitamin D-deficient and non-deficient patients in terms of mean RP duration (p = 0.0002), baseline 2-week RCS (p = 0.0001), lupus-like anticoagulant positivity (p < 0.001), NVC pattern (p < 0.001), pain visual analogue scale (VAS) (p = 0.0001), and global quality of life VAS (p = 0.0001). After adjustment for age and sex, baseline 2-week RCS remained significantly associated with vitamin D deficiency. In addition, RCS significantly decreased during follow-up among vitamin D-deficient patients who received supplementation of cholecalciferol. Conclusions: Vitamin D deficiency may be common in pediatric idiopathic RP and pinpoint its severity: our exploratory study supports the routine assessment of vitamin D in children and adolescents with severe forms of RP, warranting prospective randomized controlled trials to determine whether correction of vitamin D deficiency may potentially improve disease severity.